Eksplorasi Nilai Pendidikan dan Musik Internal serta Musik Eskternal dalam Kesenian Randai - Dinda Fatimatuz Zahra; Herlinda Herlinda; Eka Puspita Rini; Feby Oriza Sativa; Desvia Mulya Putri; Diana Sapta (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study explores the educational values ​​and internal and external musical elements contained in Randai art, one of the traditional performing arts typical of Minangkabau. Randai art not only functions as entertainment, but also as a medium for learning social, cultural, and moral values ​​for the community. This study uses a literature review approach and the initial step taken is to conduct a comprehensive literature review of educational values ​​and internal and external music in Randai art. The results of the study show that educational values ​​in Randai include teachings about togetherness, leadership, respect for customs, and social ethics. Meanwhile, internal music in Randai consists of traditional instruments such as saluang, gendang, and talempong which are integrated with dialogue and silat movements. External music plays a role in supporting the dramatic atmosphere and conveying moral messages to the audience.